Everyday Learning in an Information Society: Towards a New Totalitarianism - Peter Jarvis (Adult Education Research Conference, 2007)
It is argued here that capitalist society is a new form of totalitarianism without having the political power to enforce its will: through advertising and indoctrinational techniques we learn everyday to conform to its demands. How can critical adult education respond to this new condition?